Pretreatments to enhance the anaerobic biodegradability of Chlorella protothecoides algal biomass. Issue 1 (21st July 2017) - Ayala‐Parra, Pedro; Liu, Yuanzhe; Sierra‐Alvarez, Reyes; Field, Jim A.
Abstract : Anaerobic digestion (AD) is a promising approach for the recovery of energy and nutrients from microalgae biomass, but the process is limited by the resistance of the thick algal cell wall to biodegradation. This study investigated the effect of sonication, thermal, and alkaline pretreatments to improve methane (CH4 ) production and nitrogen release during AD of Chlorella protothecoides algal biomass. C. protothecoides is a promising feedstock for biofuel production because it can accumulate high lipid levels. Sonication experiments at 20 kHz indicated that increasing power level enhanced organic matter solubilization, CH4 production, and nitrogen released during AD of the pretreated biomass. Sonication under optimized conditions provided a marked increase in the CH4 yield compared with the untreated algae following AD for 41 days (327 and 146 mLSTP CH4 per gram volatile solids, respectively). Sonication also led to 4.1‐fold increase in ammonia N release. In contrast, thermal and alkaline pretreatment showed limited potential to improve CH4 production and N release. The results indicated that AD of sonicated C. protothecoides biomass is a promising approach to generate CH4 gas, a valuable fuel material, and release nutrients that can be recycled to meet the high fertilizer demand of algal cultivation systems. © 2017 American Institute of Chemical Engineers Environ Prog, 37: 418–424, 2018